Hubungan Tingkat Pengetahuan dengan Perilaku Konsumsi Tablet Fe saat Menstruasi pada Mahasiswi FKM UNAIR Surabaya - Rohmanur Izzani (Universitas Airlangga, 2018)
Anemia is one of the health problems in the world especially in developing countries and it is estimated that 30% of the world population suffers from anemia. Anemia is one of the health problems that often occur in pregnant women and young women. According to WHO (2013), the prevalence of anemia in the world reaches 40–88%. According to Riskesdas (2013) got anemia patients in adolescent girls amounted to 2.7%. One cause of high rates of anemia in adolescent girls is the lack of awareness of consumption of Fe tablets during menstruation. Consciousness of Fe tablet consumption during menstruation can not be separated from information and knowledge, because of knowledge is one of several factors that influence one's consumption behavior. The purpose of this study was to determine the relationship between knowledge with adolescent attitudes about consumption of Fe tablet during menstruation on students of Faculty of Public Health Unair Surabaya. This research was analytic with cross sectional approach. The samples were 50 respondents taken by simple random sampling technique. The instrument used a questionnaire. The result of this research was chi-square statistic test with significance level α = 0,05 or 95%. Statistical test results obtained p value = 1 < α = 0.05. The conclusion of this research is that there is no significant relationship of knowledge with attitude of Fe tablet consumption during menstruation on students of Faculty of Public Health Unair Surabaya.